A generic static analyzer for multithreaded Java programs. (9th May 2012) - Ferrara, P.
SUMMARY: In this paper, we present C heckmate, the first generic static analyzer of multithreadedJava programs based on abstract interpretation. C heckmate can be tuned at different levels of precision and efficiency in order to prove various properties (e.g., absence of divisions by zero and data races), and it is sound for multithreaded programs. It supports all the most relevant features of Java multithreading, such as dynamic thread creation, runtime creation of monitors, and dynamic allocation of memory. The experimental results demonstrate that C heckmate is accurate and efficient enough to analyze programs with some thousands of statements and a potentially infinite number of threads. Copyright © 2012 John Wiley & Sons, Ltd.